Integrating The Local Wisdom of Bulusan Kudus Into A P5 E-Module : A Feasibility and Practicality Study for Elementary School Students - Pratiwi, Ika Ari; Lutfiyah, Tauffiqul; Fardani, Much Arsyad (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop a project-based e-module for the co-curricular learning of the Pancasila Student Profile Strengthening Project (P5), focusing on the local wisdom of Bulusan, Kudus. The study used a Research and Development (RnD) method with the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. The study involved fifth-grade elementary students as research subjects. The research used validation questionnaires to assess the feasibility of content (material) and media (design), as well as response questionnaires to gather feedback from both students and teachers. Data analysis techniques employed descriptive and qualitative methods. Results indicate that the developed learning media met the â€œExtremely Feasibleâ€ criteria, with a content expert score of 93.75% and a media expert score of 99.03%. Both teachers and students rated the media as â€œextremely practical,â€ with practicality scores of 95% and 96.51%, respectively. These results confirm that the P5 e-module featuring Bulusanâ€™s local wisdom is both feasible and practical for use in P5 learning. The results of the study on the development of e-module P5 integrate local wisdom as an alternative to learning innovation in a contextual and meaningful way. The implication is that learning is more effective, students have a deep understanding of Bulusan local wisdom. For teachers, this E-module P5 is a reference in developing local wisdom teaching materials in elementary schools.